2021
DOI: 10.3389/fcvm.2020.591326
|View full text |Cite
|
Sign up to set email alerts
|

Hemodynamic Relevance of Anomalous Coronary Arteries Originating From the Opposite Sinus of Valsalva-In Search of the Evidence

Abstract: Coronary artery anomalies (CAA) represent a heterogeneous group of congenital disorders of the arterial coronary circulation, defined by an anomalous origin of the coronary ostium and/or vessel course. Of particular interest are anomalous coronary arteries originating from the opposite sinus of Valsalva (ACAOS). The interarterial variants (with the anomalous vessel situated between the great arteries) are historically called “malignant,” based on an anticipated higher risk for myocardial ischemia and sudden ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
49
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(49 citation statements)
references
References 112 publications
0
49
0
Order By: Relevance
“…Another study also added volume infusion to improve real-life exercise conditions. 10 The impact of cardiac stress on both the inter-arterial route of the RCA and myocardial ischaemia was examined by using dobutamine stress IVUS, FFR, and CFVR. Intravascular ultrasound has already proven to be highly sensitive to measure cross-sectional area of a stenosis.…”
Section: Discussionmentioning
confidence: 99%
“…Another study also added volume infusion to improve real-life exercise conditions. 10 The impact of cardiac stress on both the inter-arterial route of the RCA and myocardial ischaemia was examined by using dobutamine stress IVUS, FFR, and CFVR. Intravascular ultrasound has already proven to be highly sensitive to measure cross-sectional area of a stenosis.…”
Section: Discussionmentioning
confidence: 99%
“…In the setting of AAOCA associated ischemia, future research should also take into account the functional (dynamic) consequences of these anatomical features and correlate CTA findings with functional evaluation at rest and during (physical) stress using a.o. intravascular ultrasound and fractional flow reserve assessment ( 32 ). Adrenalin and dobutamine infusions can be used to mimic physical exercise stress (increasing heart rate and stroke volume) according to the previously published protocols ( 32 , 33 ).…”
Section: Limitations and Future Perspectivesmentioning
confidence: 99%
“…intravascular ultrasound and fractional flow reserve assessment ( 32 ). Adrenalin and dobutamine infusions can be used to mimic physical exercise stress (increasing heart rate and stroke volume) according to the previously published protocols ( 32 , 33 ). Multicenter studies with standardized preoperative and follow-up protocols are essential in this.…”
Section: Limitations and Future Perspectivesmentioning
confidence: 99%
“…All types of AAOCA are associated with increased risks of myocardial ischemia and SAD, especially in young athletes [ 8 ]. Studies have reported that the anomalous origin of RCA is more common than the anomalous origin of LCA [ 9 ], while the anomalous origin of LCA carries a higher risk of SAD [ 10 ].…”
Section: Introductionmentioning
confidence: 99%